The relationship between balance and spatiotemporal gait factors with quality of life in below-knee amputees - Mahboubeh Moini; elham shirzad; mohammad alizadeh (Sport Sciences and Health Research)
Background: Losing a limb can negatively impact balance and gait, leading to reduced quality of life.Aim: This study aimed to examine correlations between spatiotemporal gait and balance with scores of the Quality of Life questionnaire.Materials and Methods: 30 veterans with unilateral below-knee amputations underwent gait analysis to measure step length, stride length, stance time, cadence, velocity, and walking symmetry index by step length. Static balance was assessed via the center of pressure path length by Wii Balance Board during standing. The Timed Up and Go test evaluated dynamic balance. The QoL scores were recorded using the Quality of Life questionnaire for amputees, Trinity Amputation, and Prosthesis Experience Scales (TAPES). Pearson’s correlation coefficients were calculated between spatiotemporal of gait, balance scores, and TAPES domain outcomes.Results: Stride length (r=0.660), prosthetic step length (r=0.648) and intact step length (r=0.618) showed significant moderate positive correlations with psychosocial adjustment, while amputation limb stance time (r=-0.409) correlated weakly. Activity limitations negatively correlated with step/stride lengths (r range -0.781 to -0.784) and cadence (r=-0.538). Moreover, prosthesis satisfaction was associated with improved walking symmetry (r=0.445) and prosthetic stance time (r=0.388).Conclusion: Optimizing gait and balance in below-knee amputation can improve quality of life. Biomechanical factors should be targeted in rehab programs to enhance well-being.